Photoperiod effects on carcass traits, meat quality, and stress response in heart and lung of broilers - Baykalir, Y.; Simsek, U. G.; Erisir, M.; Otlu, O.; Gungoren, G.; Gungoren, A.; Aslan, S. (South African Journal of Animal Sciences, 2020)
This study evaluated effects of photoperiod treatments on slaughter and carcass traits, meat quality, indicators of oxidative stress, and heat shock protein 70 (Hsp70) levels of lung and heart tissues in broilers. Five hundred Ross 308 broiler chicks were used. The treatments consisted of 23 hours of continuous light and one hour of darkness (23L1D), four hours of light followed by two hours of darkness (4L2D), eight hours of light and four hours of darkness (8L4D), and 16 hours of light and eight hours of darkness (16L8D). After 42 days, two birds from each replicate were slaughtered. Birds that had been subjected to 16L8D had lower slaughter, carcass, and breast weights than the other treatments. Significant correlations were observed for slaughter, carcass and breast weights and white stripe. At 10 min post mortem, the pH of the breast was the highest in 23L1D. Breasts from birds subjected to 23L1D and 16L8D had most fat and least protein, while white striping was not different among treatments. The 4L2D treatment resulted in the highest lung glutathione (GSH) concentration. Malondialdehyde (MDA) and GSH concentrations in the heart tissues of broilers from 8L4D and 4L2D were greater than those from 23L1D and 16:8. Glutathione peroxidase (GSH-Px) and superoxide dismutase concentrations were greatest for birds subjected to 16L8D. Heat shock protein 70 was lowest in lung and heart from birds subjected to 8L4D. Thus, shorter and more frequent periods of darkness can be recommended for welfare with little compromise in performance.
Keywords: carcass quality; heat shock protein 70; oxidative stress; white stripe